PENGARUH MINAT, KEPERCAYAAN DIRI, DAN KREATIVITAS BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA - Devi Setyowati; I Wayan Widana (FPMIPA IKIP PGRI Bali, 2016)
The Effect Of Interest, Self Confidence, And Creativity Learning Toward Mathematical Learning Outcomes The main purpose of this research was to know about interest, self confidence, and creativity learning and their effect toward mathematical learning outcomes. This reaserch classified to ex post facto research. The population of this research was student tenth grade of SMA Negeri 1 Sukawati as many as 381 students. The sample was determined by simple random sampling technique with randomization was done to class not to individual. Data was collected by interest questionnaire, self confidence questionnaire, creativity learning questionnaire, and mathematical study result test. Data was analyzed by path analysis. The result of research indicate that: 1)interest have direct effect toward mathematical learning outcomes, 2) self confidence have direct effect toward mathematical learning outcomes, 3) creativity learning have direct effect toward mathematical learning outcomes, 4) self confidence have direct effect toward creativity learning, and interest, 5) self confidence, and creativity learning have direct effect simultaneously toward mathematical learning outcomes. Based on this result of research, the teacher should comprehend that difference of internal aspect who the student have influence their way to comprehend the teacher directive so teacher expected able to give motivation the student for increase the internal aspect in order that mathematical study result be increased.